Q. 33.6( 17 Votes )

If<span lang="EN-

Answer :

Given


We need to prove that x = f(y).


We have


y(bx – a) = ax – b


bxy – ay = ax – b


bxy – ax = ay – b


x(by – a) = ay – b



x = f(y)


Thus, x = f(y).


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Let A = {–1, 0, 1RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Let <span lang="EMathematics - Exemplar

Let <span lang="EMathematics - Exemplar

Express the functRD Sharma - Mathematics

Let <span lang="EMathematics - Exemplar

. Let f:(2,RS Aggarwal - Mathematics

. Let f: R RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Find the values oMathematics - Exemplar